Intermolecular alkyl radical addition to methyl 2-(2,6-Dichlorophenyl)-2H-azirine-3-carboxylate - Lemos, A. (2012)
The 2H-azirine 1 acts as an effective radical acceptor for secondary and tertiary alkyl iodides mediated by triethylborane. The addition proceeds with high regio- and diastereo-selectivity.